Opportunities of E-Governance in Dhangadi Sub-Metropolitan City: Enhancing Efficiency and Effectiveness of Municipal Administration and Staff (Patan Pragya, 2025)
This article examines the significant opportunities presented by e-governance in enhancing the efficiency and effectiveness of municipal administration and staff within Dhangadi Sub Metropolitan City, Nepal. Drawing upon empirical findings from a recent study by Sharma (2025), this analysis highlights key areas where digital transformation has demonstrably improved operational capabilities, service delivery mechanisms, and overall administrative performance. Specifically, the article explores the positive impacts of robust ICT infrastructure, the strategic utilization of official websites and email systems, the successful integration of various software solutions, and the notable improvements in service delivery and communication. While acknowledging the nascent stage of e-governance in Nepal, the findings underscore the transformative potential of digital tools to streamline processes, reduce costs, improve communication, and foster greater accountability, thereby creating a more responsive and effective municipal government for its citizens.